Estrogen-mediated differential protein regulation and signal transduction in rheumatoid arthritis. (9th May 2022) - Chakraborty, Debolina; Sarkar, Ashish; Mann, Sonia; , Monu; Agnihotri, Prachi; Saquib, Mohd; Malik, Swati; Kumavat, Rajkamal; Mathur, Anushka; Biswas, Sagarika
Abstract : Exploration of the dual and opposing facets of estrogen necessitates a clear understanding to diminish the controversy of estrogen regulation in averting the systemic, autoimmune, joint degrading disorder, and rheumatoid arthritis (RA). Experimental evidences consider estrogen as a pivotal enzyme to modulate the disease progression via managing several cellular mechanisms targeting inflammatory markers such as TNF, ILs, nuclear factor kappa B, and other regulatory proteins like matrix metalloproteinases impeding joint erosion and cartilage degradation. Estrogen modulates cellular signaling associated with inflammation, oxidative stress, related cardiovascular risk, and miRNA regulation during RA progression. Studies determining estrogen regulation in RA complicate the resemblance of the outcome as they represent both hyper and hypo level of estrogen is linked to the disease. Although some reports deliver estrogen as malign, there is now increasing evidence of rendering protection dose dependently. Variation in estrogen level causes differential expression of certain proteins and their related signaling which is directly or indirectly linked to RA pathogenesis. This review summarizes the variations in protein expression levels by focusing on the in vitro, in vivo, and clinical studies of estrogen deficiency and treatment. Construction of protein–protein interaction network, GO, and KEGG pathway enrichment analysis of the differentially expressed proteins assist in hypothesizing a potential molecular mechanism of estrogen in RA via in silico studies. Targeting these differential proteins can emerge a new path for developing advanced therapeutic strategies.